Band-edge field enhanced nonlinear cross-polarized wave generation in photonic band-gap structure - Surawut Wicharn; Prathan Buranasiri (My University, 2019)
We report on the enhancement of nonlinear cross-polarized wave (XPW) generation in a one-dimensional photonic band-gap structure, which is composed of two periodic arrangements of barium-fluoride and silicon-dioxide through numerical simulations. By detuning the pump-field wavelength to the band-edge position of the photonic band-gap spectrum, the electric field at this wavelength would be resonant and then the field enhancement mechanism arises immediately. Under band-edge field enhancement condition, we found that the conversion efficiencies of XPW generation was implicitly enhanced even without phase-matched condition from the exact angle of crystallographic axis orientation.
Keywords: Photonic Crystals and Applications